LANDREFORM SEBAGAI SOLUSI MASALAH KETIMPANGAN PEMILIKAN DAN PENGUASAAN TANAH - Citra Dewi, Marini (AKTUALITA, 2011)
Implementation of the land reform program is an effort made by each countryto make changes in land ownership and increased productivity. One of themost important land reform programs is the implementation of landredistribution. The land distribution to the farmers in redistribution programdistinguished between the solid and dense area. If the governments implementit well, then there are no more people who do not have land.Keywords: Land reform for the greatest prosperity of the people.